2005
DOI: 10.1002/ijc.21269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CXCR3 and CXCR4 expression in primary melanoma

Abstract: Tumor cell migration involved in metastases is a tightly regulated, nonrandom process. Chemokines have been identified as critical molecules guiding cell migration. We performed a prospective study to analyze a possible association between the expression of chemokine receptors CXCR3 and CXCR4 by primary melanoma and clinical outcome. Forty primary melanomas were available for analysis; 57% of the tumors expressed CXCR3 and 35% expressed CXCR4 by melanoma cells. At initial diagnosis, 5 patients had subclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 25 publications
(32 reference statements)
2
52
0
Order By: Relevance
“…Paired analysis of mRNAs and proteins in tissue and serum might provide evidence to resolve this discrepancy. As CXCL11 has distinct immunoregulatory functions, in contrast to immunostimulatory functions mediated by CXCL9 and CXCL10 (24,25), we prefer the following nonmutually exclusive explanations of how CXCL11, even in the presence of CXCL9 and CXCL10, may limit T-cell effector function as a part of negative feedback loop: (i) disrupting chemokine gradients for directional migration of T cells (26), (ii) preventing CXCR3-CXCL9/10 interaction by promoting receptor internalization (24), (iii) suppressing T-cell responses through induction and/or recruitment of regulatory T cells (25,27), and (iv) promoting growth and metastasis of tumors expressing CXCR3 (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Paired analysis of mRNAs and proteins in tissue and serum might provide evidence to resolve this discrepancy. As CXCL11 has distinct immunoregulatory functions, in contrast to immunostimulatory functions mediated by CXCL9 and CXCL10 (24,25), we prefer the following nonmutually exclusive explanations of how CXCL11, even in the presence of CXCL9 and CXCL10, may limit T-cell effector function as a part of negative feedback loop: (i) disrupting chemokine gradients for directional migration of T cells (26), (ii) preventing CXCR3-CXCL9/10 interaction by promoting receptor internalization (24), (iii) suppressing T-cell responses through induction and/or recruitment of regulatory T cells (25,27), and (iv) promoting growth and metastasis of tumors expressing CXCR3 (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that CXCL12-triggered up-regulation of MT1-MMP expression and function on these cells contributed to increase in invasion and that Rac and Rho controlled this up-regulation. Importantly, CXCR4 expression on malignant melanoma predicts poor prognosis (11,14). The present study addressed several important points for a better characterization of signaling events and MMP activities that are involved in CXCL12-promoted melanoma cell invasion.…”
Section: Introductionmentioning
confidence: 94%
“…Importantly, inhibition of CXCL12/CXCR4 interactions impairs metastasis of human breast cancer cells into regional lymph nodes and lung in mice, and expression of CXCR4 on murine B16 melanoma cells correlated with enhanced pulmonary and lymph node metastatic potential (3,8). Further in vivo studies of tumor cell metastasis in mice together with clinical data indicate that CXCR4 expression conveys tumor cell invasiveness and patient poor prognosis in a variety of solid cancer types (9)(10)(11)(12)(13)(14). CXCL12/ CXCR4 interaction is likely important not only for tumor cell invasion but also for tumor growth (10,15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CXCL9 and CXCL10 induce the migration and invasion of melanoma cell lines and multiple myeloma cells [185][186][187]. CXCR3, the receptor for CXCL9 and CXCL10 was shown to be expressed by cancer cells of solid tumors, such as breast tumor cells, renal carcinoma cells and melanoma cells [185,[188][189][190]. A direct role for CXCR3 in inducing tumor cell migration to metastatic sites was suggested by observations showing that the expression of this chemokine receptor by melanoma cells is causally involved in metastasis to lymph nodes [187].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%